Unveiling Mesenchymal Stem Cells' Regenerative Potential in Clinical Applications: Insights in miRNA and lncRNA Implications - Jankowski, Maurycy; Farzaneh, Maryam; Ghaedrahmati, Farhoodeh; Shirvaliloo, Milad; Moalemnia, Arash; Kulus, Magdalena; Ziemak, Hanna; Chwarzyński, Mikołaj; Dzięgiel, Piotr; Zabel, Maciej; Piotrowska-Kempisty, Hanna; Bukowska, Dorota; et al. (Cells, 2023)
It is now widely recognized that mesenchymal stem cells (MSCs) possess the capacity to differentiate into a wide array of cell types. Numerous studies have identified the role of lncRNA in the regulation of MSC differentiation. It is important to elucidate the role and interplay of microRNAs (miRNAs) and long non-coding RNAs (lncRNAs) in the regulation of signalling pathways that govern MSC function. Furthermore, miRNAs and lncRNAs are important clinical for innovative strategies aimed at addressing a wide spectrum of existing and emerging disease. Hence it is important to consider their impact on MSC function and differentiation. Examining the data available in public databases, we have collected the literature containing the latest discoveries pertaining to human stem cells and their potential in both fundamental research and clinical applications. Furthermore, we have compiled completed clinical studies that revolve around the application of MSCs, shedding light on the opportunities presented by harnessing the regulatory potential of miRNAs and lncRNAs. This exploration of the therapeutic possibilities offered by miRNAs and lncRNAs within MSCs unveils exciting prospects for the development of precision therapies and personalized treatment approaches. Ultimately, these advancements promise to augment the efficacy of regenerative strategies and produce positive outcomes for patients. As research in this field continues to evolve, it is imperative to explore and exploit the vast potential of miRNAs and lncRNAs as therapeutic agents. The findings provide a solid basis for ongoing investigations, fuelling the quest to fully unlock the regenerative potential of MSCs.
Keywords: RNA dlouhá nekódující; buněčná diferenciace; mesenchymal stem cells; osteoblasty; lncRNA; mikro RNA; Humans; lidé; Osteoblasts; miRNA; mezenchymální kmenové buňky; Mesenchymal Stem Cells; Cell Differentiation; RNA, Long Noncoding; MicroRNAs